Successful Teaching of Radiobiology Students in the Medical Management of Acute Radiation Effects From Real Case Histories Using Clinical Signs and Symptoms and Taking Advantage of Recently Developed Software Tools. Issue 1 (July 2018) - Majewski, Matthäus; Combs, Stephanie E.; Trott, Klaus-Rüdiger; Abend, Michael; Port, Matthias
Abstract : Abstract: In 2015, the Bundeswehr Institute of Radiobiology organized a North Atlantic Treaty Organization exercise to examine the significance of clinical signs and symptoms for the prediction of late-occurring acute radiation syndrome. Cases were generated using either the Medical Treatment Protocols for Radiation Accident Victims (METREPOL, n = 167) system or using real-case descriptions extracted from a database system for evaluation and archiving of radiation accidents based on case histories (SEARCH, n = 24). The cases ranged from unexposed [response category 0 (RC 0, n = 89)] to mild (RC 1, n = 45), moderate (RC 2, n = 19), severe (RC 3, n = 20), and lethal (RC 4, n = 18) acute radiation syndrome. During the previous exercise, expert teams successfully predicted hematological acute radiation syndrome severity, determined whether hospitalization was required, and gave treatment recommendations, taking advantage of different software tools developed by the North Atlantic Treaty Organization teams. The authors provided the same data set to radiobiology students who were introduced to the medical management of acute effects after radiation exposure and the software tools during a class lasting 15 h. Corresponding to the previous results, difficulties in the discrimination between RC 0/RC 1 and RC 3/RC 4, as well as a systematic underestimation of RC 1 and RC 2, were observed. Nevertheless, after merging reported response categories into clinically relevant groups (RC 0–1, RC 2–3, and RC 3–4), it was found that the majority of cases (95.2% ± 2.2 standard deviations) were correctly identified and that 94.7% (±2.6 standard deviations) developing acute radiation syndrome and z96.4% (±1.6 standard deviations) requiring hospitalization were identified correctly. Two out of three student teams also provided a dose estimate. These results are comparable to the best-performing team of the 2015 North Atlantic Treaty Organization exercise (response category: 92.5%; acute radiation syndrome: 95.8%; hospitalization: 96.3%).